2012
DOI: 10.1364/oe.20.021635
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observations of channel reciprocity in single-mode free-space optical links

Abstract: This article describes observations made during a recent series of single-mode lasercom experiments in which high-rate data transmission was demonstrated between a small aircraft and a ground station separated by distances up to 80 km. A significant result of the subsequent data analysis was the discovery of near-unity correlations between the signal fluctuations observed by power monitors at the two ends of the link. This evidence of reciprocity is presented, along with the description of a preliminary concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…A more effective solution to this challenge is provided by the reciprocity of a single-mode link through the atmosphere. The atmosphere has been shown both theoretically [48][49][50][51] and through measurements of amplitude fluctuations [51,52] to be reciprocal for propagation times shorter than the coherence time of the turbulence. In Ref.…”
Section: Implications For Stability and Accuracy Of One-way Opticamentioning
confidence: 99%
“…A more effective solution to this challenge is provided by the reciprocity of a single-mode link through the atmosphere. The atmosphere has been shown both theoretically [48][49][50][51] and through measurements of amplitude fluctuations [51,52] to be reciprocal for propagation times shorter than the coherence time of the turbulence. In Ref.…”
Section: Implications For Stability and Accuracy Of One-way Opticamentioning
confidence: 99%
“…Theoretical studies performed in the 70s showed that atmospheric turbulence has a reciprocal nature [267], [268], meaning that two laser beams propagating in opposite directions experience the same atmospheric turbulence distortions. Atmospheric turbulence reciprocity was later confirmed experimentally [269], [270]. Through reciprocity, a pilot signal from a receiver can be used at a transmitter to provide channel state information (CSI), and based on this, various strategies may be adopted at the transmission terminal, including adaptive modulation, varying bit rate, and beam phase and amplitude pre-compensation [267].…”
Section: B Atmospheric Turbulence Effects Mitigationmentioning
confidence: 94%
“…Theoretical studies in the '70s revealed that atmospheric turbulence has a reciprocal nature [18], [19], meaning that two laser beams propagating in opposite directions experience the same atmospheric turbulence distortions. Atmospheric turbulence reciprocity has been later confirmed experimentally [20], [21]. Through reciprocity in FSO, a pilot signal from a receiver can be used at the transmitter end to provide channel state information (CSI), based on which the transmitter end could employ various digital signal processing (DSP) techniques.…”
Section: Introductionmentioning
confidence: 93%